Enteral supplementation with probiotics in preterm infants: A retrospective cohort study and 6-year follow-up - Brown, Beth Ellen; Huisman, Esther; Miller, Michael R.; Ulrich, Cindy; Reid, Gregor; da Silva, Orlando (Frontiers in Nutrition, 2022)
The objective of this retrospective cohort study was to assess the impact of an enteral probiotics supplementation protocol on the incidence of necrotizing enterocolitis (NEC) in infants born <33 weeks gestational age (GA) or birth weight (BW) <1500g. In addition, a six-year follow-up is presented after instigation of probiotic use. In October 2014, our NICU introduced an enteral probiotics supplementation protocol for infants born <33 weeks GA or BW <1500g. Infants received 0.5g of Bifidobacterium breve HA-129, Lacticaseibacillus rhamnosus HA-111, Bifidobacterium bifidum HA-132, Bifidobacterium longum subsp. infantis HA-116, and Bifidobacterium longum subsp. longum HA-135 (FloraBABY) daily until discharge or transfer from hospital. The incidence of NEC was compared among infants for two years pre- and post implementation of the protocol then six-years following continuous implementation of the probiotic use. In total, 370 infants not treated with probiotics between 2012 and 2014 were included with an incidence of NEC at 4.9%. In comparison, the 367 infants who received had a 67% reduction (4.9% to 1.6%, p=0.01) in our Neonatal Intensive Care Unit (NICU). The results remained significant (aOR=0.26; 95% CI: 0.09, 0.72; p<0.01) after adjusting for GA, small for gestational age, and antenatal corticosteroid use. Data from the Canadian Neonatal Network not only showed a consistently high rate of NEC in October 2014, but also identified exceedingly high rates (8.7-15.6%) in some hospitals up to 2021, while our rates have been consistently low with using the probiotic as standard therapy for low BW premature babies, with no serious side effects reported. In conclusion, the introduction of a five-strain probiotic natural health product has coincided with a reduced the incidence and complications of NEC in our NICU setting.